Child poverty, status of rural women and education in sub Saharan Africa. (April 2020) - Ingutia, Rose; Rezitis, Anthony N.; Sumelius, John
Highlights: Factors affecting child poverty in sub Saharan Africa. Three Stages Least Squares simultaneous equations and fixed effects method. Crop production index greatly affects primary school enrolment and child underweight. Improvement of women's status in agriculture is key to child poverty reduction. Good institutional quality enables children and women to access basic needs. Abstract: Africa's disadvantaged children are often rural, malnourished, out of school, child brides or child labourers. Moreover, they tend to have illiterate mothers who have been denied access to productive resources. Our objective is to analyse the factors affecting child poverty. To this end, we studied the endogenous variables of under-five mortality rate, primary-school enrolment and child underweight. Endogeneity led to the use of Three Stages Least Squares simultaneous equations and fixed effects methods. The estimated elasticities indicate that female employment in agriculture has the greatest effect on under-five mortality rates, while the crop production index exerts the greatest effect on primary school enrolment and child underweight. The elasticity ranking demonstrates that what is at issue is not the effect of education on reducing child poverty or the effect of child poverty on reducing education, but the improvement of the status of women, particularly in the agricultural sector. Furthermore, policies for long-lasting solutions should highlight institutional quality as a prerequisite in child poverty reduction and present children and women with equal opportunities to satisfy basic needs and access productive resources.